An approach to wind-induced fatigue analysis of wind turbine tubular towers. (March 2020) - Huo, Tao; Tong, Lewei
Abstract: This study discusses the wind-induced fatigue analysis of typical pitch-controlled 1.25MW wind turbine structures, with the reasonable consideration of the influence of low stress range fatigue damage, wind direction and the rotating effect of the blades. An integrated finite element model consisting of blades, nacelle, tower and foundation is established in ANSYS software. The wind speed and wind direction joint distribution function at the construction site of the wind turbine structures based on the observation datum of the meteorological station in China is put forward. The wind-induced response time history analyses of the tubular tower structures corresponding to different wind speed and wind direction cases are conducted. Finally, the wind-induced fatigue analysis theory of the tubular tower structures based on the time domain and time-frequency domain method are systematically established. The results indicate that the rotating effect of the blades should be considered in the fatigue life analysis of the tubular towers. Neglecting the influence of the wind direction and the low stress range on the fatigue damage of the tubular towers could lead to the decreased fatigue life which is conservative but not economic. Compared with the time domain method, the fatigue life of the tubular tower based on time-frequency domain method decreases, but the calculation is simpler. Adopting the equivalent stress range method considering rain flow correction to conduct the fatigue analysis of the tubular tower is recommended in this study. Highlights: We established an integrated FE model of wind turbine structures including rotor, nacelle, tubular tower and foundation. We developed a wind-induced response model of wind turbine structures with different speeds and directions. We verified the accuracy of the proposed wind-induced response model by comparison with the existing field test data. We considered the impact of low stress range, wind direction and the blade rotating effect on the fatigue damage. We recommended using the equivalent stress range method considering rain flow correction to conduct the fatigue analysis.